The Potential Impact of Entomology on Large Animal Veterinary Practice in Texas - Hesseltine, Elise B. (My University, 2020)
On March 23, 2020, I began an internship with Circle T Veterinary Services, which is a mobile veterinary service based in Sandia, Texas. From March to August, I traveled with Dr. Tobin Pennington to farms and ranches across South Texas conducting large animal farm calls. Dr. Pennington is the sole owner and practitioner of Circle T Veterinary Services, which he opened in 2012. It is a 100% mobile service, operating completely out of Dr. Pennington’s truck. Circle T covers a large part of South Texas, with clients residing as north as Oakville, west to Cotulla, east to Rockport, and as south as McAllen. A typical day working at Circle T Veterinary Services starts early in the morning, depending on how far we need to travel to make it to the first call. There is routine work to be completed, such as palpating and deworming cows, castrating calves, vaccinating horses, equine dental floats, and more. I have been able to witness a wide variety of illness and injuries, like broken legs, horses with nasopharyngeal cicatrix syndrome, bovine fetal extractions and fetotomy, and corneal ulcers. Emergencies, such as equine colic or lacerations occur often and must be treated quickly. In one day, we may travel hundreds of miles across South Texas. In this paper, I examine the interconnections between veterinary medicine and another interest of mine, entomology. As a student in the Entomology Minor curriculum at Kansas State University, I have taken great interest in the study of insects and their effects on agriculture, ecosystems, and disease transmission. I wanted to explore the effects of arthropods on veterinary medicine because I plan on pursuing a DVM (Doctor of Veterinary Medicine) degree in the future. Below, I took experiences from my internship and researched them further, creating an in-depth look at the interactions between entomology and veterinary practice. I included a case study that I observed during my internship, which piqued my interest in West Nile Encephalomyelitis. The remainder of this paper then focuses on prevention strategies for several vector-borne diseases and emerging threats to the cattle industry. This analysis demonstrates my passion for entomology